Evaluation of the effectiveness of a 3-year, teacher-led Healthy Lifestyle Program on eating behaviors among adolescents living in day school hostels in Malaysia - Teng, Chian Yi; Chin, Yit Siew; Mohd Taib, Mohd Nasir; Chan, Yoke Mun (2018)
Background: Independence gained during adolescence may be associated with unhealthy eating behaviors. Although malnutrition among adolescents is evident, studies on eating behaviors among adolescents are scarce. Objective: To determine the effectiveness of a teacher-led Healthy Lifestyle Program on eating behaviors among adolescents in Malaysia. Methods: This was a cluster randomized controlled trial (conducted in 2012 to 2014), with 100 schools randomly selected from 721 schools, then assigned to 50 intervention schools and 50 control schools. A Healthy Eating and Be Active among Teens (HEBAT) module was developed for pretrained teachers to deliver a Healthy Lifestyle Program on eating behaviors among adolescents. Eating behaviors of the respondents was determined using Eating Behaviors Questionnaire. Linear Mixed Model analysis and χ2 test were used to determine within- and between-group effects of studied variables. Results: A total of 4277 respondents participated in this study, with 2635 samples involved in the final analysis, comprised of 921 intervention and 1714 control respondents. There were 32.4% (36.4%) males and 67.6% (63.6%) females in the intervention (control) group. Mean age was comparable between the groups (intervention = 12.98 years; control = 12.97 years). Majority of the respondents skipped meals at baseline (intervention = 74.7%; control = 79.5%). After the program, intervention respondents had higher consumption frequency of lunch, dinner, and mid-morning snack but a lower consumption frequency of late-evening snack and meal skipping behaviors than their control counterparts. Conclusion: The teacher-led Healthy Lifestyle Program was effective in reducing meal-skipping behaviors among Malaysian adolescents.